Progreso genético para calidad de grano de arroz (Oryza sativa L.) mediante selección recurrente - Martínez, César Pomplio; Carabali, Silvio James; Borrero, Jaime; Duque, Myriam Cristina; Silva, James (CIAT, 2018)
Arroz-Oryza sativa